2015
DOI: 10.1017/s1463423615000286
|View full text |Cite
|
Sign up to set email alerts
|

Working with primary care clinicians and patients to introduce strategies for increasing referrals for pulmonary rehabilitation

Abstract: Background: Pulmonary rehabilitation (PR), a programme of exercise, education and psycho-social support, is recommended for patients with chronic obstructive pulmonary disease but referral rates are relatively low compared with need. Aim: Working with primary care clinicians (GPs and practice nurses) from eight practices, this project developed strategies for influencing clinician and patient behaviours as a means of increasing referral rates for PR. Methods: A participatory action research design was employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(75 citation statements)
references
References 13 publications
(33 reference statements)
1
63
0
Order By: Relevance
“…Thirty-five studies reported on referral rates [3,7,; 28 of these were observational studies [3,7,[12][13][14][16][17][18][19][20][21][22][23][25][26][27][28][29][30][31][34][35][36][37][40][41][42]44], while the remaining seven assessed the effect of an intervention on COPD care (and measured referral rates at baseline and post-intervention) [15,24,32,33,38,39,43]. Nine studies reported on HCP perceived barriers to PR referral [23,26,[45][46][47][48][49][50][51], and seven of these also reported on enablers [23,26,45,…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Thirty-five studies reported on referral rates [3,7,; 28 of these were observational studies [3,7,[12][13][14][16][17][18][19][20][21][22][23][25][26][27][28][29][30][31][34][35][36][37][40][41][42]44], while the remaining seven assessed the effect of an intervention on COPD care (and measured referral rates at baseline and post-intervention) [15,24,32,33,38,39,43]. Nine studies reported on HCP perceived barriers to PR referral [23,26,[45][46][47][48][49][50][51], and seven of these also reported on enablers [23,26,45,…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Patients are frequently not being referred to these services 12,21,26,47,50,55 and even if they are, there are considerable barriers that must be overcome in order for the patients to be able to attend pulmonary rehabilitation. Healthcare providers need to be educated about pulmonary rehabilitation and the evidence that supports its benefits in patients with a wide degree of chronic as well as malignant conditions.…”
Section: Discussionmentioning
confidence: 99%
“…11 Another studied indicated that poor communication among health care professionals and with patients as to what pulmonary rehabilitation is and how it can benefit patients, frequently occurs. 12,26 Patients complained that health care providers were not taking the time to explain their condition and offer solutions. Contributing to this problem was that some patients felt their general practitioners had lim-pulmonary Research and respiratory medicinE ISSN 2377ISSN -1658 Pulm Res Respir Med Open J ited knowledge about pulmonary rehabilitation and they were therefore not told of the benefits of rehabilitation or simply not referred to these programs at all.…”
Section: Barriers To Pulmonary Rehabilitation In Palliative Carementioning
confidence: 99%
See 2 more Smart Citations